2002
DOI: 10.5172/jamh.1.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Parents with psychosis: a pilot study examining self-report measures related to family functioning

Abstract: AeJAMH is an academic publication. Its sole purpose is the dissemination of knowledge for the advancement of mental health, to as wide an audience as possible. Thus the journal is free to access by individuals and institutions. All published material is made available for the purposes of personal, educational or research activities. No further reproduction or distribution of the articles in whole or in part should proceed without the permission of the publisher. Any use of the material for other purposes, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
0
17
1
Order By: Relevance
“…Several previous studies have investigated parenting outcomes in psychosis (e.g. Dolman et al, 2013;Plant et al, 2002), however, this research tends to regard the parenting abilities of mothers who already have psychosis whereas the mediation model in the current study suggests that parenting emotional experiences may also predict levels of sub-clinical psychotic phenomena. The current study used a non-clinical population rather than a clinical sample, but due to the link between schizotypy and psychosis our findings suggest that the model should be tested in a clinical sample.…”
Section: Discussioncontrasting
confidence: 41%
“…Several previous studies have investigated parenting outcomes in psychosis (e.g. Dolman et al, 2013;Plant et al, 2002), however, this research tends to regard the parenting abilities of mothers who already have psychosis whereas the mediation model in the current study suggests that parenting emotional experiences may also predict levels of sub-clinical psychotic phenomena. The current study used a non-clinical population rather than a clinical sample, but due to the link between schizotypy and psychosis our findings suggest that the model should be tested in a clinical sample.…”
Section: Discussioncontrasting
confidence: 41%
“…Lastly, the self-report results portray that: "Nearly a half of the participants in this study reported high levels of parenting stress, and a third reported low levels of satisfaction in their role. Fourteen percent rated their own parenting skills as 'poor'' [8].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it's possible to claim that, relevant to parents experiencing psychosis, parental behaviour such as distorted expressions of reality or strange behaviour/beliefs portray the root for children experiencing anxious, confused, perplexed relationship with their parents and additionally attachment problems [7]. Likewise, Plant, et al [8] indicates that: "The interaction between psychosis and family functioning has been an area of considerable interest to researchers. Apart from the familial properties of schizophrenia and affective psychoses, having a family member with a mental illness, places considerable stress on the family system" [9].…”
Section: Psychosis and Parentingmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence also exists that these issues do not arise solely at a regional level, but must be taken in the context of the significant fears parents have expressed elsewhere about losing their children should they highlight difficulties at home (Diaz-Caneja & Johnson, 2004;Plant et al, 2002;Stanley & Penhale, 1999).…”
Section: The Psychological Impact Of Parental Mental Health Difficultmentioning
confidence: 96%